Modeling of acetate-type fermentation of sugar-containing wastewater under acidic pH conditions. (January 2018) - Huang, Liang; Pan, Xin-Rong; Wang, Ya-Zhou; Li, Chen-Xuan; Chen, Chang-Bin; Zhao, Quan-Bao; Mu, Yang; Yu, Han-Qing; Li, Wen-Wei
Graphical abstract: Highlights: The model provides insights on the acetate-type fermentation process at acidic PH. Key factors governing pH-dependency of the AD fermentation pathway were revealed. Acetate and butyrate production was thermodynamically more favorable at pH 5.0. Optimal HRT for acetate production from sucrose fermentation was predicted. Abstract: In this study, a kinetic model was developed based on Anaerobic Digestion Model No. 1 to provide insights into the directed production of acetate and methane from sugar-containing wastewater under low pH conditions. The model sufficiently described the dynamics of liquid-phase and gaseous products in an anaerobic membrane bioreactor by comprehensively considering the syntrophic bioconversion steps of sucrose hydrolysis, acidogenesis, acetogenesis and methanogenesis under acidic pH conditions. The modeling results revealed a significant pH-dependency of hydrogenotrophic methanogenesis and ethanol-producing processes that govern the sucrose fermentative pathway through changing the hydrogen yield. The reaction thermodynamics of such acetate-type fermentation were evaluated, and the implications for process optimization by adjusting the hydraulic retention time were discussed. This work sheds light on the acid-stimulated acetate-type fermentation process and may lay a foundation for optimization of resource-oriented processes for treatment of food wastewater.